PEMBELAJARAN DENGAN PENDEKATAN KONTEKSTUAL UNTUK MENINGKATKAN KEMAMPUAN KOMUNIKASI MATEMATIS SISWA - Muhsin; Zulfa Razi (Jurnal Numeracy, 2019)
Mathematical communication skills are very important abilities possessed by students in the process of learning mathematics, especially in understanding mathematics. One important goal in mathematics learning is that students are able to provide arguments for their answers and provide responses to answers given by others, and what is being learned becomes more meaningful to them. Mathematical communication is essential from teaching, learning and acsess mathematics, we will need communication if we want to reach in full the purpose such as understanding. Therefore, it is very important to develop and improve students' mathematical communication skills in the learning process of mathematics. This study aims to examine the improvement of mathematical communication skills between students who get learning with contextual approaches and students who get conventional learning. This research is an experimental study using a pre-test post-test control group design. The population in this study were eighth grade students of MTsN 4 Pidie, Aceh in the 2018/2019 academic year. Through Purposive Sampling, two parallel classes were chosen, namely class VIII1 as the experimental class and VIII2 as the control class. The instrument used to collect research data is a test of mathematical communication skills. The statistical test used t test to analyze data on increasing mathematical communication skills. The results of the studyshowed that the improvement of mathematical communication skills of students who obtained learning with contextual approaches was better than students who obtained conventional learning. Abstrak Kemampuan komunikasi matematis merupakan kemampuan yang sangat penting dimiliki oleh siswa dalam proses pembelajaran matematika khususnya dalam memahami matematika. Salah satu tujuan penting dalam pembelajaran matematika bahwa siswa mampu memberikan argumen atas jawabannya serta memberikan tanggapan atas jawaban yang diberikan oleh orang lain, serta apa yang sedang dipelajari menjadi lebih bermakna baginya. Komunikasi matematis merupakan hal esensial dari mengajar, belajar dan meng-acsess matematika, kita akan memerlukan komunikasi jika hendak meraih secara penuh tujuan seperti memahamai. Oleh karena itu, sangat penting untuk mengembangkan dan meningkatkan kemampuan komunikasi matematis siswa dalam proses pembelajaran matematika. Penelitian ini bertujuan untuk mengkaji peningkatkan kemampuan komunikasi matematis antara siswa yang memperoleh pembelajaran dengan pendekatan kontekstual dan siswa yang memperoleh pembelajaran konvensional. Penelitian ini merupakan penelitian eksperimen dengan menggunakan desain pre-test post-test control group design. Populasi dalam penelitian ini adalah siswa kelas VIII MTsN 4 Pidie, Aceh pada tahun pelajaran 2018/2019. Melalui Purposive Sampling dipilihlah dua kelas secara paralel yaitu kelas VIII1 sebagai kelas eksperimen dan VIII2 sebagai kelas kontrol. Instrumen yang digunakan untuk mengumpulkan data penelitian berupa tes kemampuan komunikasi matematis. Uji statistik yang digunakan adalah uji-t untuk menganalisis data peningkatan kemampuan komunikasi matematis. Hasil penelitian menunjukkan bahwa peningkatan kemampuan komunikasi matematis siswa yang memperoleh pembelajaran dengan pendekatan kontekstual lebih baik daripada siswa yang memperoleh pembelajaran konvensional. Kata kunci: Kemampuan Komunikasi Matematis, Pendekatan Kontekstual